An Analysis of Surgically Treated Thyroid in a Tertiary Care Centre - Yadav, Rohit; Jain, Amar; Ahmad, Zeeshanuddin (British Journal of Healthcare and Medical Research, 2022)
Introduction: Thyroid cancer is one of the most common malignant endocrine glands worldwide. Greater than 75% of cases occur in women making this the fifth most common malignancy in women. Although less than 25% of thyroid carcinomas occur in men, men account for 45% of mortality from thyroid carcinoma. Surgery is the mainstay in the management of thyroid cancer. Surgical outcomes need to be tempered against the excellent prognosis of the disease. Objectives: This study was carried out to evaluate the demographic features, histologic spectrum, type of surgery performed and postoperative complications of surgically treated thyroid disease. Material & Methods: This study was conducted in Department of General Surgery, Chirayu Medical College and Hospital, Bhopal and included those patients who underwent thyroid surgery from January 2018 to March 2022. Results: A total of 123 thyroidectomies (in 104 females and 19 males) for various thyroid disorders were performed, of which total thyroidectomy was the predominant surgery in 64% of patients. The commonest malignancy and benign lesion encountered was follicular variant of papillary thyroid carcinoma and multinodular goitre respectively. Conclusions: Thyroid cancer, even with advanced disease, is eminently treatable. Surgery forms the crux of treatment of thyroid diseases. Aggressive histology, the extent of thyroid surgery, distant metastasis and age are important factors, which should be factored in the algorithm of thyroid cancer management.